PENINGKATAN MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA PEGAWAI PADA KELURAHAN ARDIREJO DAN KELURAHAN MIMBAAN KECAMATAN PANJI KABUPATEN SITUBONDO - Andriawan, Dio Bagus; Karnadi, Karnadi; Minullah, Minullah (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
Human resources are individuals capable of and willing to assist an organization in achieving its goals. The purpose of this research is to determine the improvement of motivation, work discipline, and job satisfaction, as well as the performance of human resources in Ardirejo Village and Mimbaan Village of Panji Sub-District. The population in this study consists of all employees of Ardirejo Village and Mimbaan Village in Panji Sub-District, totaling 38 employees, both civil servants (ASN) and non-civil servants. The sampling technique is determined by purposive sampling. The data analysis and hypothesis testing of this research employed Partial Least Square-Structural Equation Modeling (PLS-SEM). The results of hypothesis testing for direct effects using Smart PLS 3.0 application indicate that motivation has a significant positive influence on job satisfaction. Work discipline has a negative influence on job satisfaction, but it is not significant. Motivation has a significant positive influence on performance. Work discipline has a negative influence on performance, but it is not significant. Job satisfaction has a negative influence on performance, but it is not significant. The results of hypothesis testing for indirect effects show that motivation does not significantly affect performance through job satisfaction. Work discipline does not significantly affect performance through job satisfaction.